Diagram of Model 12-101 Vacuum System - Bendix Corporation (1970)
Schematic diagram depicting the vacuum system for a Bendix Model 12-101 Time-of-Flight Mass Spectrometer. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Mass spectrometers; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Spectrometer industry